Functional characterization of S100A8 and S100A9 in altering monolayer permeability of human umbilical endothelial cells. - Liqun Wang; Haihua Luo; Xiaohuan Chen; Yong Jiang; Qiaobing Huang (PLoS ONE)
S100A8, S100A9 and S100A8/A9 complexes have been known as important endogenous damage-associated molecular pattern (DAMP) proteins. But the pathophysiological roles of S100A8, S100A9 and S100A8/A9 in cardiovascular diseases are incompletely explained. In this present study, the effects of homo S100A8, S100A9 and their hetero-complex S100A8/A9 on endothelial barrier function were tested respectively in cultured human umbilical venous endothelial cells (HUVECs). The involvement of TLR4 and RAGE were observed by using inhibitor of TLR4 and blocking antibody of RAGE. The clarification of different MAPK subtypes in S100A8/A9-induced endothelial response was implemented by using specific inhibitors. The calcium-dependency was detected in the absence of Ca2+ or in the presence of gradient-dose Ca2+. The results showed that S100A8, S100A9 and S100A8/A9 could induce F-actin and ZO-1 disorganization in HUVECs and evoked the increases of HUVEC monolayer permeability in a dose- and time-dependent manner. The effects of S100A8, S100A9 and S100A8/A9 on endothelial barrier function depended on the activation of p38 and ERK1/2 signal pathways through receptors TLR4 and RAGE. Most importantly, we revealed the preference of S100A8 on TLR4 and S100A9 on RAGE in HUVECs. The results also showed the calcium dependency in S100A8- and S100A9-evoked endothelial response, indicating that calcium dependency on formation of S100A8 or A9 dimmers might be the prerequisite for this endothelial functional alteration.